PERANCANGAN SISTEM INFORMASI AKUNTANSI PENCATATAN KAS PADA KLINIK ANDINA KARAWANG - Muhammad Edi Iswanto; Arif Maulana Yusuf; Joko Irawan; Vera Wati (LPPM Universitas Dhyana Pura, 2026)
The purpose of this research is to design and develop a web-based accounting information system for Klinik Andina Karawang to improve the process of recording cash inflows and outflows. The system is intended to enable a more structured and efficient financial documentation process. It was developed to replace the previously utilized manual recording methods, which were prone to errors, data loss, delays, and inconsistencies in financial reporting. This research adopts the Design Science Research Methodology (DSRM), which comprises six stages: problem identification, objective definition, system design and development, demonstration, evaluation, and communication. The outcome of this research is a fully implemented system, as verified through functional testing and user validation. These evaluations indicate that the system’s features functioned as expected and contributed positively to improving operational efficiency.